Spatial and multivariate assessment of access to water for sustainable agriculture intensification in semi-arid Ghana - Boateng, E. N. K.; Atampugre, Gerald; Mariwah, S.; Mensah, I.; Johnson, F. A.; Furst, C.; Nyarko, B. K. (2024)
Climate change, population growth, rapid urbanization, shifting dietary patterns, and economic development pose significant challenges to food security, particularly in the Global South. Addressing these challenges involves efforts aimed at sustainable agricultural intensification (SAI), especially for smallholder farmers in marginalized regions. However, knowledge gaps persist regarding smallholder farmers’ access to water for SAI, particularly in arid and semi-arid agroecological zones. This study investigates smallholder farmers’ access to water for SAI in the Guinea and Sudan Savannah Agroecological Zones (SSAZ) of Ghana. Data were collected from 698 smallholder farmers across 25 communities using a structured questionnaire and geospatial techniques. The analysis employed cost distance analysis, factor analysis, and multinomial-ordered logistic regression. Findings indicate that the average distance travelled to access water from a dam or a river was 11 km and 9 km, respectively. Most respondents reported low to moderate water access for SAI. Key factors influencing water access included soil type, vegetation, and the distances to dams and rivers. To improve water access, it is recommended that smallholder farmers be educated on effective soil and water conservation techniques. Additionally, both government and non-governmental organizations should focus on building community-level dams to increase water availability for sustainable agricultural intensification.